PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL BERBASIS QUIZIZZ PADA PEMBELAJARAN IPS KELAS V SEKOLAH DASAR - Zahra Febria Ardila; Syifaul Hayah; Ulfa Hanum; Vanya Alea Zuhura; Yuliani Fitri; Susi Ratna Sari (STKIP Subang, 2026)
This study aims to investigate the use of digital learning media in increasing fifth-grade students' learning interest in Social Studies (IPS) at the elementary school level. The approach used in this study is literature analysis, in which researchers collected and studied various relevant literature sources, including articles, journals, and books that discuss digital learning media and students' learning interest. The findings of this study indicate that the application of digital learning media in elementary school is of digital learning media, such as interactive videos, educational applications, and online learning platforms, can significantly increase students' interest in IPS. Various studies reviewed indicate that digital media is effective in attracting students' attention, increasing participation, and facilitating the understanding of IPS concepts more effectively. These results indicate that the use of digital learning media can be considered an efficient approach to increasing students' learning interest, especially in IPS subjects in elementary schools. This research is expected to contribute to the development of more innovative and engaging learning methods for students. Quizizz allows for automatic adjustment of question difficulty levels, provides real-time feedback, and increases student engagement in the learning process